Analisis Pengelolaan Kelas Oleh Guru PAK Dan Budi Pekerti Dalam Meningkatkan Minat Belajar Siswa Kelas XI SMA Negeri 2 Tebing Tinggi Tahun Pembelajaran 2023/2024 - Ray Gibrael Sinaga; Tiurma Berasa; Simion Harianja (Simpati, 2023)
The aim of this research is to determine the achievements of classroom management carried out by PAK teachers in increasing the learning interest of class XI students at SMA Negeri 2 Tebing Tinggi for the 2023/2024 academic year. The research hypothesis is that classroom management by PAK and Budi Pekerti teachers will increase the learning interest of class. Hypothesis testing using the t test formula obtained the value tcount=4.091>ttable=2.021. The tcount value is in the curve area of ​​rejection of H0 and acceptance of Ha. Thus, it can be concluded that the research hypothesis is accepted, namely classroom management by PAK and Budi Pekerti teachers in increasing the interest in learning of class The achievement of classroom management by PAK and Budi Pekerti teachers in increasing the interest in learning of class.